Theory of the folklore text - Bralina, S.Zh. (KSU publ., 2016)
In the article the concept of the folklore text is scrutinized. For this purpose textologic, semiotic, functional peculiarities of the folklore text are revealed. History of science makes us see that folklore study for a long time actively has been using the category of text. But the notion itself in the sphere of folklore study gained different interpretations, reaching far beyond the borders of textual study. Evolution of the notion «folklore text», its functional and semantic reevaluation has in the basis common processes of development, existing as in folklore itself, so in the science treating it. Investigation concerning the problem of traditional and modern folklore, its identification features, types and peculiarities of existence is the matter of conceptual importance for this article. Contemporary perception of folklore is a magnificent picture of in many ways different phenomena not confined only to cultural ones. From nominative and semantic point of view this situation is determined by different factors of ethnical, historical, scientific and educational nature. All this enables us to speak about such types of folklore as written folklore, postfolklore, antifolklore, folklore routine, verbal and non-verbal, spoken and oral culture, folklore subcultures, artistic communication within the limits of folkgroups, Netlore (folklore of Internet) etc. Special attention is paid to contemporary conceptions of folklore text. All the conceptions mentioned above, as diversified as they can be, still have something common in several positions. First of all, they state that folklore text is different from literary one. Hence takes its origin common tendency among researchers to widen borders of text space in folklore and treat it with taking into consideration facts, analyzed by other humanitarian sciences.
Фольклор мəтінінің теориясы
Теория фольклорного текста
Keywords: folklore; postfolklore; folklore text; folklore textual study; folklore tradition; variant of the folklore text; semiotic text; verbal culture; linguistic folklore study; ethnolinguistics